Analysis of the Effect of Labor, Domestic Investment, and Inflation on GRDP in Lampung Province 1991 – 2020 - Nur Miranda Risang Ayu; Asih Murwiati; Dedy Yuliawan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this study was to determine the effect of labor, domestic investment, and inflation on GRDP in Lampung Province in 1991 – 2020. Data analysis was carried out descriptively quantitatively using the (OLS) Multiple Linear Regression method. Secondary data were obtained from the Central Statistics Agency of Lampung Province. The results of this study indicate that labor has a positive and significant effect on GRDP in Lampung Province. Meanwhile, domestic investment has a positive but insignificant effect and inflation has a negative and insignificant effect on GRDP in Lampung Province.